(untitled) (Global Journal of Human-Social Science, 2024)
The book, comprising 21 standalone chapters from 35 contributors, explores inclusivity in higher education assessments through societal, institutional, and interpersonal perspectives. It emphasizes the need for assessment practices that cater to diverse student populations, considering factors beyond traditional demographics. The review highlights the book’s strengths, including its multi-author approach, practical examples, and incorporation of indigenous knowledge. However, it also notes weaknesses such as a lack of field-specific guidelines and limited practical narratives. The book contributes significantly to assessment literature, offering valuable insights for researchers, educators, and policymakers seeking to develop more inclusive assessment practices in higher education. This review analyzes the book’s main arguments, strengths, weaknesses, and potential audience, providing a comprehensive overview of its content and relevance in the field of educational assessment.